Information systems application to improve the financial statements presentation (Case study of PT XYZ) - Rindiani, Rindiani; Angelita, Salsa; Alfarez, Rifqy Aufa; Rosnidah, Ida; Krisdiana, Krisdiana (Indonesian Journal of Multidisciplinary Science, 2024)
This study aims to know and analyze the application of sales information systems and accounting information systems that aim to improve the quality of financial statements. This study uses descriptive qualitative research methods by comparing theory and practice/implementation of information systems at PT XYZ. The main focus of this study is how to apply the sales information system and the accounting information system so that the process of preparing financial statements, especially income statements, balance sheets, changes in capital and cash flow statements, can be presented on time to management. The research results are as follows: (1) The manual process of transfer of sales data to Accurate Online resulted in delays in the preparation of financial statement, affecting management's ability to make decisions based on up-to-date financial information. (2) The new system improves inventory control, smoother returns, and balance sheet position. (3) The study suggests a new system for e-commerce transactions, especially online, as trends in marketplaces like Shopee, Tokopedia, and TikTok have significantly impacted Indonesian shopping.